2016
DOI: 10.7324/japs.2016.60727
|View full text |Cite
|
Sign up to set email alerts
|

Potential radical-scavenging activity of Pouteria caimito leaves extracts

Abstract: Pouteria caimito (Sapotaceae) is widely distributed throughout Latin America, including Brazil. The yellow fruits, known as abiu, caimito, or abiurana, are eaten in natura or used to prepare desserts. In addition to being a commercially available Brazilian fruit, P. caimito has also been used as a traditional medicine. Therefore, hexane, ethanol, and aqueous extracts from its leaves were evaluated for radical-scavenging activity. Free radical-scavenging activity was tested using the DPPH assay. Total phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
7
0
3
Order By: Relevance
“…This study found the strong antioxidant activity using DPPH assay in four different concentrations (25 µg, 50 µg, 75 µg, and 100 µg). The results were similar to the antioxidant activity results that were reported in earlier studies [21] , [22] , [23] , [24] . In addition to this, the reducing power activity directly reflects the antioxidant capacity of the sample [25] , [26] .…”
Section: Discussionsupporting
confidence: 91%
“…This study found the strong antioxidant activity using DPPH assay in four different concentrations (25 µg, 50 µg, 75 µg, and 100 µg). The results were similar to the antioxidant activity results that were reported in earlier studies [21] , [22] , [23] , [24] . In addition to this, the reducing power activity directly reflects the antioxidant capacity of the sample [25] , [26] .…”
Section: Discussionsupporting
confidence: 91%
“…Pouteria caimito (leaves): Antioxydant proanthocyanidin and anti-inflammatory terpenes (spinasterol) have already been identified in leaf extracts, but no antiviral activity has been mentioned before (França et al, 2016).…”
Section: Scleria Microcarpa and Astrocaryum Jauarimentioning
confidence: 99%
“… 2003 ) and are eaten raw or used to prepare desserts (Franca et al. 2016 ). With the increasing impact of human activities on the environment, the wild germplasm resources of abiu fruit have sharply decreased, and these germplasm resources are imperiled.…”
mentioning
confidence: 99%
“…The fruit is also called yellow star apple, blueberry pie fruit and cauje. Abiu fruit are rich in tryptophan, threonine, lysine, Vitamin C, Vitamin B3 and other nutrients (Maia et al 2003) and are eaten raw or used to prepare desserts (Franca et al 2016). With the increasing impact of human activities on the environment, the wild germplasm resources of abiu fruit have sharply decreased, and these germplasm resources are imperiled.…”
mentioning
confidence: 99%